The effect of small incision lenticule extraction on contrast sensitivity - Yue, Pinqing; Wang, Zeng; Wu, Di; Zhang, Hua; Zhang, Pan (Frontiers in Neuroscience, 2023)
The improvements due to small incision lenticule extraction (SMILE) in vision, e.g., in spherical equivalent (SE) and visual acuity (VA), has been widely recognized. However, the contrast sensitivity (CS) change after SMILE was not certain. Here, we investigated the effect of SMILE on CS before, 1 day after and 7 days after surgery and then clarified the corresponding mechanism by using a perceptual template model (PTM). In addition, the relationship among SE, VA, and CS was discussed. The quick contrast sensitivity function (qCSF) was applied to measure CS with high precision and accuracy. We found that (1) CS was significantly improved 1 day after SMILE and was also increased 7 days after the surgery, (2) CS improvements were dependent on spatial frequency and external noise, (3) the increase in CS was due to the decreased internal additive noise and an enhanced perceptual template, and (4) Greater SE improvements predicted better VA improvements 1 day after SMILE, and a positive correlation between SE improvements and AULCSF improvements 7 days after SMILE was observed. These findings help us better understand the effect of SMILE and provide effective indicators for future visual research.